Industrial concentration and performance a study of the structure, conduct and performance of Indian - Kambhampati Uma S (Delhi OUP, 1996)
This book is one of few studies on the microeconomic performance of Indian industry. It tackles questions relating to the nature of competition in Indian industry- whether the private sector in India is concentrated and whether firms in concentrated priva
Keywords: India; Industries